2010
DOI: 10.1080/09540120903111437
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on commercial sex behaviors among male clients in Sichuan Province, China

Abstract: Males who seek commercial sex have been identified as an important “bridging population” in the transmission of HIV. There is little information on the HIV-related risk perceptions and behaviors among commercial sex male clients (CSMCs) in China. This study reports qualitative findings from six focus groups and 41 in-depth interviews with CSMCs in Sichuan Province, China. Commercial sex visits were described as a group activity and associated with patterns of social-network specific interactions and norms. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
2
31
1
Order By: Relevance
“…A prior qualitative study in Sichuan province 36 revealed that, despite the availability of condoms in pharmacies and sex shops in China, many male clients were still inhibited by the social embarrassment of being caught with a condom. Consequently, many male clients relied on condoms available in the commercial sex venues.…”
Section: Discussionmentioning
confidence: 98%
“…A prior qualitative study in Sichuan province 36 revealed that, despite the availability of condoms in pharmacies and sex shops in China, many male clients were still inhibited by the social embarrassment of being caught with a condom. Consequently, many male clients relied on condoms available in the commercial sex venues.…”
Section: Discussionmentioning
confidence: 98%
“…The majority of participants raised concern about STIs (sexually transmitted infections), especially when considering South African sex workers. This was not a recurring theme in reviewed international literature, where male clients often did not use protection and seemed unperturbed by the dangers of unprotected sexual activities (Goldenberg, Strathdee, Gallardo, Rhodes, Wagner, & Patterson, 2011;Yang et al, 2010). Fear of disease may be more prevalent in South Africa, because South Africa has one of the highest levels of HIV infection in the world, an estimated 5.2 million people (approximately 12%), making it likely that South African participants may be more mindful of contracting the virus (Morrell, Jewkes, & Lindegger, 2012).…”
Section: Deterrents In Paying For Sexmentioning
confidence: 99%
“…Such a definition of masculine sexuality may actually contribute to the conditions that perpetuate sex work, as men may come to define sex work as a natural outcome of their intrinsic sex drive (Hernandez-Truyol & Larson, 2006;Raymond, 2003). Visits to sex workers are often constructed as a normative social group activity, and although men are not forced into participating, the group may covertly coerce an individual into participating by creating an accepting normative setting (Yang, Latkin, Liu, Nelson, Wang, & Luan, 2010). Often visits to sex workers are considered a bonding experience with friends, an opportunity for business networking or as a rite of passage into manhood where men can prove their sexual adequacy to their peers (Peng, 2007;Yen, 2008).…”
Section: Social Constructions Around Paying For Sexmentioning
confidence: 99%
See 2 more Smart Citations